The dark side of the “employment miracle” in the USA - Wolfgang Cornetz (Intereconomics, 1988)
Whereas in Europe the creation of jobs in the United States has been hailed as an “employment miracle”, in the USA itself there is concern mainly about the negative implications of the considerable increase in employment. A trend towards deindustrialisation, poor productivity and growing wage inequality are issues that are being discussed in this connection.
Keywords: 330